Satisfaction With Life, Satisfaction With Job, and the Level of Care Rationing Among Polish Nurses—A Cross-Sectional Study - Kołtuniuk, Aleksandra; Witczak, Izabela; Młynarska, Agnieszka; Czajor, Karolina; Uchmanowicz, Izabella (Frontiers in Psychology, 2021)
Background: Rationing of nursing care is a serious issue that has been widely discussed throughout recent years in many countries. The level of satisfaction with life and of satisfaction with job as the nurse-related factors may significantly affect the level of care rationing. Aim: To assess the rationing of nursing care among the Polish nurses and the impact of nurse-related variables, i.e., satisfaction with life and satisfaction with job on the level of nursing care rationing. Materials and Methods: A cross-sectional study was conducted among 529 Polish registered nurses employing in two University Hospitals. Three self-report scales in the Polish version were used in this study, namely, Basel Extent of Rationing of Nursing Care-revised version (BERNCA-R), Satisfaction with Life Scale (SWLS), and Satisfaction with Work Scale (SWWS). Results: The respondents indicated that the most frequently rationed activity is studying the situation of individual patients and care plans at the beginning of the shift. The least frequently rationed activity indicated by the respondents was adequate hand hygiene. The patient-to-nurse ratio and the level of satisfaction with job are significant independent factors affecting the level of care rationing. Conclusions: The assessment of the level of satisfaction with life and identification of factors affecting this assessment will enable reducing the occurrence of care rationing.